Profiling astrophysically relevant MgC4H chains: an attempt to aid astronomical observations - Bâldea, Ioan (Monthly notices of the Royal Astronomical Society, 2020)
In this paper, we report results of an extensive theoretical study on MgC4H chains conducted at DFT and CCSD(T) levels motivated by the recent discovery of this species in IRC+10216. A detailed characterization of both neutral and charged species is presented, which include structural, chemical bonding and vibrational properties, rotational, centrifugal distortion and Watson l-type doubling constants, dipole moments, Fermi contact, and spin-rotation constants. In addition, we present ab initio estimates needed for subsequent astrochemical evolution modelling (e.g. dissociation energies, acidity, electron attachment, and ionization energies and related chemical reactivity indices). Possible formation pathways are also discussed. They comprise exchange, (radiative) association, dissociative recombination, and ion neutralization reactions. As an important result aiming at stimulating further observational searching, we suggest that MgC4H− anions should also be observable via rovibrational spectroscopy. The reason is twofold: (i) Neutral MgC4H0 chains possess a sufficiently large dipole moment consistent with dipole-bound anion states and large electron attachment cross-sections. (ii) MgC4H− anions possess a dipole substantially larger than MgC4H0 neutrals (and also larger than that estimated earlier for the longest astronomically detected C8H− anion). This makes MgC4H− anion intensities in rovibrational spectrum experimentally accessible even in the unlikely case of a relative abundance MgC4H−/MgC4H0 comparable to that of CH4, whose anion has the lowest relative abundance observed so far in space because weakly polar C4H0 chains do not support dipole-bound anion states. A suggestion on why, counterintuitively, the MgC2H abundance found in IRC+10216 was lower than that of the longer MgC4H is also presented.
Gesehen am 11.12.2020
Im Titel ist die Ziffer "4" tiefgestellt